UKHLS input data for UKMOD (2010-2019) - Patryk Bronka; Daria Popova; Matteo Richiardi (University of Essex, Centre for Microsimulation and Policy Analysis (CeMPA), 2023)
This report introduces a new version of UKMOD that uses the UK Household Longitudinal Study (UKHLS) data as its input dataset. UKHLS is a large panel survey with a sample of approximately 40,000 households in its first wave. UKHLS contains detailed income data and a wide range of demographic and labour market information. As such it is the primary survey of interest in the UK for those interested in longitudinal analysis. The longitudinal version of UKMOD that runs on UKHLS data covers the period 2010-2019 (waves 1-11). While building the UKMOD input data using the UKHLS dataset, the main aim was to re-create as closely as possible UKMOD input data variables that are based on FRS. When running policy simulations, users have an option of running UKMOD either with the FRS dataset (default option) or with UKHLS dataset. The UKMOD version based on UKHLS data maintains all the flexibility of UKMOD: policy scenarios can be created by implementing not only parametric changes, but also more structural reforms, and benefits from all existing UKMOD tools and add-ons that facilitate scenario analysis.
Keywords: 330; Microsimulation; Public Policy; Welfare Benefits; Taxation; Life Course Analysis; Households